The ERβ5 splice variant increases oestrogen responsiveness of ERαpos Ishikawa cells. Issue 2 (February 2020) - Collins, Frances; Itani, Nozomi; Esnal-Zufiaurre, Arantza; Gibson, Douglas A; Fitzgerald, Carol; Saunders, Philippa T K
Abstract : Endometrial cancer is a common gynaeological malignancy: life time exposure to oestrogen is a key risk factor. Oestrogen action is mediated by receptors encoded by ESR1 (ERα) and ESR2 (ERβ): ERα plays a key role in regulating endometrial cell proliferation. A truncated splice variant isoform (ERβ5) encoded by ESR2 is highly expressed in cancers. This study explored whether ERβ5 alters oestrogen responsiveness of endometrial epithelial cells. Immunhistochemistry profiling of human endometrial cancer tissue biopsies identified epithelial cells co-expressing ERβ5 and ERα in stage I endometrial adenocarcinomas and post menopausal endometrium. Induced co-expression of ERβ5 in ERα pos endometrial cancer cells (Ishikawa) significantly increased ligand-dependent activation of an ERE-luciferase reporter stimulated by either E2 or the ERα-selective agonist 1, 3, 5-(4-hydroxyphenyl)-4-propyl-1H-pyrazole (PPT) compared to untransfected cells. Fluorescence recovery after photobleaching (FRAP) analysis of tagged yellow fluorescent protein (YFP)-ERβ5 transfected into Ishikawa cells revealed that incubation with E2 induced a transient reduction in intra-nuclear mobility characterised by punctate protein redistribution which phenocopied the behaviour of ERα following ligand activation with E2. In ERα neg MDA-MD-231 breast cancer cells, there was no E2-dependent change in mobility of YFP-ERβ5 and no activation of the ERE reporter in cells expressing ERβ5. In conclusion, we demonstrate that ERβ5 can act as heterodimeric partner to ERα in Ishikawa cells and increases their sensitivity to E2. We speculate that expression of ERβ5 in endometrial epithelial cells may increase the risk of malignant transformation and suggest that immunostaining for ERβ5 should be included in diagnostic assessment of women with early grade cancers.